A rice chloroplast‐localized ABC transporter ARG1 modulates cobalt and nickel homeostasis and contributes to photosynthetic capacity. Issue 1 (23rd June 2020) - Li, Haixiu; Liu, Yuan; Qin, Huihui; Lin, Xuelei; Tang, Ding; Wu, Zhengjing; Luo, Wei; Shen, Yi; Dong, Fengqin; Wang, Yaling; Feng, Tingting; Wang, Lili; et al.
Summary: Transport and homeostasis of transition metals in chloroplasts, which are accurately regulated to ensure supply and to prevent toxicity induced by these metals, are thus crucial for chloroplast function and photosynthetic performance. However, the mechanisms that maintain the balance of transition metals in chloroplasts remain largely unknown. We have characterized an albino‐revertible green 1 ( arg1 ) rice mutant. ARG1 encodes an evolutionarily conserved protein belonging to the ATP‐binding cassette (ABC) transporter family. Protoplast transfection and immunogold‐labelling assays showed that ARG1 is localized in the envelopes and thylakoid membranes of chloroplasts. Measurements of metal contents, metal transport, physiological and transcriptome changes revealed that ARG1 modulates cobalt (Co) and nickel (Ni) transport and homeostasis in chloroplasts to prevent excessive Co and Ni from competing with essential metal cofactors in chlorophyll and metal‐binding proteins acting in photosynthesis. Natural allelic variation in ARG1 between indica and temperate japonica subspecies of rice is coupled with their different capabilities for Co transport and Co content within chloroplasts. This variation underpins the different photosynthetic capabilities in these subspecies. Our findings link the function of the ARG1 transporter to photosynthesis, and potentially facilitate breeding of rice cultivars with improved Co homeostasis and consequently improved photosynthetic performance.